Psychological Impact of the Very Early Beginning of the COVID-19 Outbreak in Healthcare Workers: A Bayesian Study on the Italian and Swiss Perspectives - Sara Uccella; Sara Uccella; Sara Uccella; Francesco Mongelli; Pietro Majno-Hurst; Luca Jacopo Pavan; Stefano Uccella; Stefano Uccella; Cesare Zoia; Laura Uccella (Frontiers Media S.A., 2022)
BackgroundWe investigated the COVID19-related psychological impact on healthcare workers in Italy and in Italian-speaking regions of Switzerland, three weeks after its outbreak. All professional groups of public hospitals in Italy and Switzerland were asked to complete a 38 questions online survey investigating demographic, marital and working status, presence of stress symptoms and need for psychological support.ResultsWithin 38 h a total of 3,038 responses were collected. The subgroup analysis identified specific categories at risk according to age, type of work and region of origin. Critical care workers, in particular females, reported an increased number of working hours, decline in confidence in the future, presence of stress symptoms and need for psychological support. Respondents reporting stress symptoms and those with children declared a higher need for psychological support.ConclusionsThe large number of participants in such a short time indicates for a high interest on topic among health-care workers. The COVID19 outbreak has been experienced as a repeated trauma for many health-care professionals, especially among female nurses' categories. Early evidence of the need of implementating short and long-term measures to mitigate impact of the emotional burden of COVID-19 pandemic are still relevant.